Immunemorphological aspects of different variants of generalized parodontitis - Samoilenko A.V.; Shpon’ka I.S.; Babenko L.M.; Poslavs’ka O.V.; Unin Shi (Морфологія, 2013)
This article is devoted to the study of the prognostic value of immunohistochemical markers of local immune homeostasis of parodontal with definition of CD3+, CD4+, CD8+, CD20+, CD68+, CD138+ cells of the immune series and S100 + dendritic cells, angiogenesis CD34 and VEGF, reparative proliferation Ki-67, stromal degradation MMP-1 and inducible nitric oxide synthase iNOS in inflammatory processes periodontal definition of morphological relations between the values of immunohistochemical indices and aggressiveness of generalized parodontitis.